Thrombotic antiphospholipid syndrome in a woman with mixed connective tissue disease. Case report - Falconi-Toro, Daniel (2024)
Introduction: Antiphospholipid antibody syndrome is a rare systemic autoimmune disease that produces a hypercoagulable state with risk of thrombosis. The ACR/EULAR APS 2023 criteria are used for diagnosis. With respect to treatment, anticoagulants and antiplatelet agents are the most used. Mixed connective tissue disease is a systemic autoimmune disease that presents the association of clinical manifestations of other autoimmune entities. Objective: To describe the presentation of two rare autoimmune systemic diseases together, with the purpose of contributing a practical approach to diagnosis and management. Case presentation: A 37-year-old patient is described who presented an episode of pulmonary thromboembolism secondary to antiphospholipid antibody syndrome and who for 6 months had symptoms compatible with mixed connective tissue disease. The patient had to undergo surgery and subsequently responded to treatment. Discussion: This case revealed the presence of two autoimmune entities, antiphospholipid antibody syndrome and mixed connective tissue disease presented together and whose debut of complications was a pulmonary thromboembolism, also finding the presence of multiple positive autoantibodies between these antiphospholipid and anti-U1 antibodies snRNP, which represents a diagnostic challenge when differentiating between other connective tissue diseases such as systemic lupus erythematosus, cutaneous systemic sclerosis, mixed connective tissue disease and rheumatoid arthritis. The treatment decision was based on the patient's characteristics and clinical condition at the time of diagnosis. Conclusions: Antiphospholipid antibody syndrome entails the presence of a thrombotic episode; on the other hand, its association with a mixed connective tissue disease is rare and may increase its morbidity and mortality.